Intraneural Venous Malformations of the Median Nerve - González Porto, Sara Alicia; González Rodríguez, Alba; Midón Míguez, José (Archives of Plastic Surgery, 2016)
Venous malformations arising from the peripheral nerve are a rare type of vascular malformation. We present the first case of an intraneural venous malformation of the median nerve to be reported in a child and review the previous two cases of median nerve compression due to a venous malformation that have been reported. These cases presented with painless masses in the volar aspect of the wrist or with symptoms suggestive of carpal tunnel syndrome. Clinical suspicion should lead to the use of Doppler ultrasonography as the first-line diagnostic tool. Magnetic resonance imaging and histopathology can confirm the diagnosis, as phleboliths are pathognomonic of venous malformations. Surgical treatment appears to be the only modality capable of successfully controlling the growth of an intraneural malformation. Sclerotherapy and radiotherapy have never been used to treat this type of malformation.
Keywords: Hemangioma; Median nerve; Vascular malformation; Carpal tunnel syndrome